Application of Comparative Transcriptional Genomics to Identify Molecular Targets for Pediatric IBD - Fang, Kai; Grisham, Matthew B.; Kevil, Christopher G. (Frontiers in Immunology, 2015)
Experimental models of colitis in mice have been used extensively for analyzing the molecular events that occur during inflammatory bowel disease (IBD) development. However, it is uncertain to what extent the experimental models reproduce features of human IBD. This is largely due to the lack of precise methods for direct and comprehensive comparison of mouse and human inflamed colon tissue at the molecular level. Here we use global gene expression patterns of two sets of pediatric IBD and two mouse models of colitis to obtain a direct comparison of the genome signatures of mouse and human IBD. By comparing the two sets of pediatric IBD microarray data, we found 83 genes were differentially expressed in a similar manner between pediatric Crohn’s disease (CD) and ulcerative colitis (UC). Up regulation of the chemokine (C-C motif) ligand 2 (CCL2) gene that maps to 17q12, a confirmed IBD susceptibility loci, indicates that our comparison study can reveal known genetic associations with IBD. In comparing pediatric IBD and experimental colitis microarray data, we found common signatures amongst them including: 1) up regulation of CXCL9 and S100A8; 2) cytokine-cytokine receptor pathway dysregulation; and 3) over-represented IRF1 and IRF2 transcription binding sites in the promoter region of up regulated genes, and HNF1A and Lhx3 binding sites were over-represented in the promoter region of the down regulated genes. In summary, this study provides a comprehensive view of transcriptome changes between different pediatric IBD populations in comparison with different colitis models. These findings reveal several new molecular targets for further study in the regulation of colitis.